MO519: Ferric Citrate Hydrate Improves Levels of Transferrin Saturation in Hemodialysis Patients With Lower Levels of Transferrin Saturation. (3rd May 2022) - Yokoyama, Keitaro; Inoue, Ryo; Ito, Kyoko; Mitobe, Yuko; Matsumoto, Yu; Yamada, Ryoichi; Susai, Hiroyuki; Nishino, Noriaki
Abstract: BACKGROUND AND AIMS: Iron deficiency identified by transferrin saturation (TSAT) is reported as a risk factor for all-cause mortality and cardiovascular events in non-dialysis dependent (NDD) chronic kidney disease (CKD) [1, 2 ] and for all-cause mortality in hemodialysis patients [3 ]. Ferric citrate hydrate (FC, Riona ® ), an oral iron-based phosphate binder in CKD patients, is also approved as an iron preparation for iron-deficiency anemia (IDA) in Japan in 2021. In the USA, ferric citrate (Auryxia ® ) is approved as a phosphate binder for dialysis-dependent CKD and an iron replacement product for the treatment of IDA in patients with NDD-CKD. FC or ferric citrate increased TSAT in patients with NDD-CKD and IDA [4 ]. However, a few data show that whether FC or ferric citrate has the similar effect in hemodialysis patients whose TSAT is <20%. Considering the additional indication of IDA in Japan, we investigated the FC's effect on TSAT by using the data obtained from the ASTRIO study [5 ], which was conducted in Japanese hemodialysis (HD) patients. METHOD: We conducted a retrospective study using the data of ASTRIO study [5 ], which is a randomized, prospective, open-label, multicenter 24-week study to investigate the FC's effect on anemia management compared with non-iron-based phosphate binders (PBs) in Japanese HD patients with hyperphosphatemia. Ninety-three patients taking non-iron-based PBs were randomized 1:1 to continue PBs (control) or switch to FC. During 24-week study, serum phosphate and hemoglobin were controlled, 3.5–6.0 mg/dL and 10–12 g/dL, respectively. From 93 patients (FC, n = 48; control, n = 45), we extracted 41 patients (FC, n = 21; control, n = 20) whose TSAT at baseline was <20% and compared the levels of TSAT and other iron related parameters between FC group and control group. RESULTS: In the ASTRIO study, the mean (SD) levels of TSAT (%) was 14.3 (4.0) at baseline and rapidly increased to 25.0 (11.1) at 4 weeks in the FC group. After that, the levels of TSAT were almost unchanged in the FC group, whereas, in the control group, the mean (SD) levels of TSAT were almost unchanged during the 24-week study. The mean (SD) levels of serum ferritin gradually increased until week 12 and subsequently showed to be stabilized in the FC group, whereas, in the control group, these were almost unchanged during the 24-week study (Table 1 ). CONCLUSION: In Japanese HD patients whose TSAT was <20%, FC rapidly increased TSAT compared with control. We will also investigate the FC's effect on TSAT in HD patients from the post-marketing surveillance study, the prospective, multicenter and observational, up to maximum 2 years treatment.